Scanning electron and light microscopic investigation of bursa fabricius in turkey (meleagris gallopavo) - Murat Erdem Gultiken; Dincer Yildiz; Siyami Karahan; Durmus Bolat (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was postnatal investigation of morphometric features of Bursa fabricius in Turkey by using scanning electron microscope and light microscope. Materials and Methods: One 1-24 week old 50 turkeys (meleagris gallopavo) were used. Their Bursa fabriciuses were taken out after the necropsy and weighted. Tissues were fixed with glutaraldehyde, examined and photographed under scanning electron microscope. For histological examination, tissues were prepared using routine histologic methods and stained with Mallory's triple and Hematoxylen-Eosine. Results: The morphometric data concerning turkey ducklings used in the study showed that Bursa fabricius reaches its maximum size at the 9th week. The decrease in the weight of Bursa fabricius following the week of 9 proved that involution session in the turkey begins after that period. On the investigation performed by means of scanning electron microscopy, dome shaped surface epithelium which covers subepithelial lymph follicles on the surface was determined to be most clear in the 5th and 9th weeks. There was a distinct irregularity of this appearance in the following weeks (13th and 24th). Conclusion: It was concluded that the results may contribute to the researches which relate to humoral immunity formation and effectiveness of vaccination programme.